2014
DOI: 10.3233/jad-140318
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneity and Natural History of Mild Cognitive Impairment of Visual Memory Predominant Type

Abstract: We evaluate the longitudinal outcomes of amnestic mild cognitive impairment (aMCI) according to the modality of memory impairment involved. We recruited 788 aMCI patients and followed them up. aMCI patients were categorized into three groups according to the modality of memory impairment: Visual-aMCI, only visual memory impaired; Verbal-aMCI, only verbal memory impaired; and Both-aMCI, both visual and verbal memory impaired. Each aMCI group was further categorized according to the presence or absence of recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Previous studies found that the risk of progression to dementia was higher in verbal-aMCI and both-aMCI patients than in visual-aMCI patients. [10][11][12] Our results contrast with cortical thinning studies revealing left medial temporal atrophy in verbal-aMCI patients compared to NC subjects. 39 This difference may have been due to the smallness of the sample in the verbal-aMCI subgroup or nonspecific binding of [ 18 F]THK5351 in the medial temporal regions reducing its resolving power in this area.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous studies found that the risk of progression to dementia was higher in verbal-aMCI and both-aMCI patients than in visual-aMCI patients. [10][11][12] Our results contrast with cortical thinning studies revealing left medial temporal atrophy in verbal-aMCI patients compared to NC subjects. 39 This difference may have been due to the smallness of the sample in the verbal-aMCI subgroup or nonspecific binding of [ 18 F]THK5351 in the medial temporal regions reducing its resolving power in this area.…”
Section: Discussioncontrasting
confidence: 99%
“…MCI participants were diagnosed according to a modified criteria proposed by Petersen 4,38 for MCI that have been used in previous studies. 12,39 aMCI patients were defined as those with a performance below -1.0 SD of the norm in at least one of the following memory tests: Seoul Verbal Learning Test (SVLT), delayed recall; and Rey Complex Figure Test (RCFT), delayed recall. naMCI patients had task scores worse than -1.0 SD below the norm in at least one of the following tests: neuropsychological tests of language and related functions, visuospatial function, and frontal/executive function.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor performance in episodic memory tests, cognitive impairment in other domains such as frontal/executive function, and depression are all known to predict the conversion to dementia in aMCI subjects [7][8][9][10]. In fact, even among aMCI subjects, those with more severe https://doi.org/10.23838/pfm.2018.00065 Jun Pyo Kim, et al memory impairment, multi-domain cognitive deficits, or verbal memory impairment have higher dementia conversion rates than those with milder memory impairment, memory involvement only, or visual memory impairment only [3,[11][12][13]. In addition, the results of a recent meta-analysis showed that older age, female gender, hypertension, diabetes, hippocampal and medial temporal lobe atrophy, entorhinal atrophy, lower mini-mental status examination (MMSE) score, higher Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog) score, presence of the apolipoprotein E4 (ApoE4) allele, and abnormal cerebrospinal fluid tau levels are associated with the progression from aMCI to AD dementia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with verbal-aMCI showed significant cortical thinning in the left anterior and medial temporal regions compared with NC, while visual-aMCI patients did not. Furthermore, the cortical thinning pattern of the both-aMCI group included that found in the verbal-aMCI group, but was more widespread, with involvement in the bilateral temporal regions.In terms of clinical course, we evaluated the longitudinal outcomes of aMCI patients according to the modality of the memory impairment involved[13]. Patients were classified into visual-aMCI, verbal-aMCI, and both-aMCI groups, as de-scribed above.…”
mentioning
confidence: 99%